Pengaruh Karakteristik Pemimpin dan Penghargaan terhadap Motivasi Kerja dan Kinerja Karyawan (Studi pada PT Visi Karya Agritama) - Djoemadi, Farid Rokhman; Noermijati (Universitas Brawijaya, Indonesia, 2014)
This study examines the characteristics Leaders Influence and Respect Work Motivation and Employee Performance (Study on PT Vision Works Agritama). Analyzing the influence of Research Objectives and Characteristics of Leaders Award, both directly and indirectly through the work motivation on employee performance. Methods The study used a quantitative approach and survey methods, as well as the type of correlational research. This research use PLS (Partial Least Square). The population in this study were all employees of PT Vision Agritama work totaling 64 people. Furthermore, the entire population of respondents that made this study using census method in the determination of the sample. The research proves that the characteristics of leaders and a significant positive effect on employee motivation, but no significant effect on employee performance. Award no significant effect on employee motivation and employee performance. Work Motivation positive and significant impact on employee performance. Originality of this research is characteristics Award Leader and not always positive and significant effect on Employee Motivation and Performance.